Adipocytic Glutamine Synthetase Upregulation via Altered Histone Methylation Promotes 5FU Chemoresistance in Peritoneal Carcinomatosis of Colorectal Cancer - Zhang, Xuan; Li, Qing; Du, Aibei; Li, Yifei; Shi, Qing; Chen, Yanrong; Zhao, Yang; Wang, Bin; Pan, Feng (Frontiers in Oncology, 2021)
The development of resistance to 5-fluorouracil (5FU) chemotherapy is a major handicap for sustained effective treatment in peritoneal carcinomatosis (PC) of colorectal cancer (CRC). Metabolic reprogramming of adipocytes, a component of the tumor microenvironment and the main composition of peritoneum, play a significant role in drug resistance of PC, with the mechanisms being not fully understood. By performing metabolomics analysis, we identified glutamine (Gln), an important amino acid, inducing resistance to 5FU-triggered tumor suppression of CRC-PC through activating mTOR pathway. Noteworthily, genetic overexpression of glutamine synthetase (GS)in adipocytes increased chemoresistance to 5FU in vitro and in vivo while this effect was reversed by pharmacological blockage of GS. Next, We showed that methionine metabolism were enhanced in amino acid omitted from CRC-PC of GS transgenic (TgGS) mice, increasing intracellular levels of S-carboxymethy-L-cys. Moreover, loss of dimethylation at lysine 4 of histone H3 (H3k4me2) was found in adipocytes in vitro, which may lead to increased expression of GS. Furthermore, biochemical inhibition of lysine specific demethylase 1 (LSD1) restored H3k4me2, thereby reducing GS-induced chemoresistance to 5FU. Our findings indicate that GS upregulation-induced excessive of Gln in adipocytes via altered histone methylation is potential mediator of resistance to 5FU chemotherapy in patients with CRC-PC.